2002
DOI: 10.1177/073428290202000204
|View full text |Cite
|
Sign up to set email alerts
|

An Independent Confirmatory Factor Analysis of the Differential Ability Scales

Abstract: This study investigated the structure of the Differential Ability Scales (DAS; Elliott, 1990a) using confirmatory factor analysis with 130 normal school-aged children. Maximum likelihood estimation, using the six Core subtests, found an extremely good fit with the data and supported the DAS model proposed by Elliott (1990a). In addition, the six Core subtests were found to be strong measures of g, supporting their contribution to the General Conceptual Ability. Replication of Keith's (1990) final model, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Although not based on any one theory, the DAS factor structure was generally consistent with what is now often termed Cattell-HornCarroll (CHC) theory (Dunham, McIntosh, & Gridley, 2002;Keith, 1990Keith, , 2005Keith, Quirk, Schartzer & Elliott, 1999;Sanders, McIntosh, Dunham, Rothlisberg, & Finch, 2007;Stone, 1992). The second edition of the DAS is also based on multiple theories and empirical findings, but is also explicitly tied to CHC theory (Elliott, 2007).…”
Section: Instrumentmentioning
confidence: 87%
“…Although not based on any one theory, the DAS factor structure was generally consistent with what is now often termed Cattell-HornCarroll (CHC) theory (Dunham, McIntosh, & Gridley, 2002;Keith, 1990Keith, , 2005Keith, Quirk, Schartzer & Elliott, 1999;Sanders, McIntosh, Dunham, Rothlisberg, & Finch, 2007;Stone, 1992). The second edition of the DAS is also based on multiple theories and empirical findings, but is also explicitly tied to CHC theory (Elliott, 2007).…”
Section: Instrumentmentioning
confidence: 87%
“…The Verbal (Gc), Nonverbal Reasoning (Gf), and Spatial (Gv) abilities factor structure hypothesized for the DAS and DAS-II Core subtests has been validated using large standardization samples (Elliott, 1990(Elliott, , 2007; children with cultural, linguistic, or racial differences (DiCerbo & Barona, 2000;Keith, Quirk, Schartzer, & Elliott, 1999;Riccio, Ross, Boan, Jemison, & Houston, 1997); and children with developmental and learning disabilities (Dumont, Cruse, Price, & Whelley, 1996;Elliott, 2001;Gibney, McIntosh, Dean, & Dunham, 2002;Hughes & McIntosh, 2002;Kercher & Sandoval, 1991;McIntosh & Gridley, 1993;Shapiro, Buckhalt, & Herod, 1995). The structure is also supported by independent exploratory and confirmatory factor analysis (Daleo et al, 1999;Dunham, McIntosh, & Gridley, 2002;Keith, 1990). The DAS-II Introductory and Technical Handbook (Elliott, 2007) provides evidence that the Core subtest factor structure remains unchanged from the original DAS.…”
Section: Empirical Examination Of the Differential Ability Scalesmentioning
confidence: 90%
“…The DAS was developed to emphasize specific individual cognitive strengths and weaknesses as well as general intelligence. Independent validation studies found support for the intended structure of the DAS (Dunham, McIntosh, & Gridley, 2002; Keith, 1990) and showed that it measured the same constructs across its age range, 2 1 / 2 through 17 (Keith, 1990). Although designed from an eclectic theoretical orientation, the DAS factor structure was generally consistent with Cattell–Horn–Carroll (CHC) theory (cf.…”
mentioning
confidence: 99%